"Imiona" zazdrości w językach biblijnych i w wybranych językach współczesnych = "Names" of envying in biblical languages and in selected modern languages - Piekarz, Danuta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The topic of the article is the terminology that describes a human feeling having two faces: "envy" as the desire to have good that someone else has achieved and jealousy as the fear of losing a loved one. The first of these feelings was described in Latin with the word invidia, from which the names of this feeling were formed in many modern languages, especially in Romance, but also, for example, in English.
Keywords: zazdrość; zawiść; języki biblijne; języki współczesne; envy; jealousy; biblical languages; modern languages